Propuesta de un manual de seguridad y salud ocupacional para el talento humano de la empresa hormigonera Guevara Daqui-Hormigueda de la ciudad de Riobamba - Endara Larrea, Iván Fabricio (2015)
Policies, laws, standards and rules concerning the Occupational Safety and Health Industrial governing our environment, are not implemented or used properly in existing companies and industries in Ecuador; and particularly in the province of Chimborazo in Riobamba so does the company Concrete Guevara Daqui-HORMIGUEDA causing that there are many risks of accidents in the same, that is why this research topic was chosen. This research paper entitled "PROPOSAL FOR A MANUAL FOR OCCUPATIONAL SAFETY AND HEALTH HUMAN TALENT ENTERPRISE HORMIGONERA DAQUI-HORMIGUEDA DE GUEVARA Riobamba" general objective to propose a manual occupational safety and health in the Concrete Guevara company Daqui-Hormigueda of Riobamba, specific objectives and determine the situational analysis of the company; identify, measure and assess the risk factors of work; design and place signage at the respective sites; develop and articulate the industrial safety plan is properly implemented and promote industrial and occupational safety in the company. Also this work has had its full theoretical framework that has served to reinforce the information we have obtained, the methods used were analytical served to analyze the documents and information obtained in the review that indicates what are the factors and diminish risk and inductive chips used in observation, deductive it allowed expose the proposal to develop a plan for occupational safety and health and statistics to help us with the corresponding graphical representations; within the techniques used is used in observation visits and physical findings were made at the company Concrete Guevara Daqui-Hormigueda of Riobamba, the survey applied to workers, it allows the company to analyze internally, The interview was conducted by the owner manager which highlight the strengths and weaknesses of the company. In the interview we noted what the real strengths and weaknesses of the company, with the result that industrial safety and occupational health is known superficially, employees do not get the appropriate training, as has no signage to help identify hazards or precautions to be taken, has no policy or regulation to go on, you can also show that the Manager has managed to provide its employees with the necessary protective equipment and machinery indicating the risks and precautions to take when producing . Later after analysis was determined as proposed manual occupational safety and health in order to safeguard the physical and mental integrity of each employee of the company, setting the following conclusions: • HORMIGUEDA Company currently has a linear management structure, as the highest authority of the company is who is in charge of the responsibility to define the political establishment and security of all employees. With regard to standards for occupational health and safety, these do not apply, nor are issued legal guidelines to that effect met. • Administrator of the interview and survey results HORMIGUEDA workers, it was determined that the company does not have a manual safety and occupational health; that employees and workers are unable to face some kind of accident within the company, which does not have a training plan on this subject, and that the facilities are unsafe. • The risks of work, found and examined, within the company HORMIGUEDA are: Physical as noise, vibration, humidity; Chemicals have corrosive, irritant, harmful; We scored biological fungi; Ergonomic, physical fatigue have repeatedly by position, displacement, strain, load handling; and finally as the Psychosocial stress and dissatisfaction monotony. • To solve the problems encountered risks in the company accidents HORMIGUEDA a proposal for a manual of prevention in occupational safety and health and industrial safety plan that will ensure the integrity of human talent throughout the organization was raised